2021
DOI: 10.1158/1535-7163.mct-20-0619
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Intermedin (Adrenomedullin 2) Suppresses the Growth of Glioblastoma and Increases the Antitumor Activity of Temozolomide

Abstract: Glioblastoma multiforme (GBM; grade IV glioma) is the most malignant type of primary brain tumor and is characterized by rapid proliferation and invasive growth. Intermedin (IMD) is an endogenous peptide belonging to the calcitonin gene-related peptide family and has been reported to play an important role in cell survival and invasiveness in several types of cancers. In this study, we found that the expression level of IMD was positively related to the malignancy grade of gliomas. The highest expression of IM… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…ADM has been reported as one of 5 candidate genes associated with glioma resistance to TMZ, which showed to be consistently linked to higher expression of DDIT4 and lower prognosis in TMZ-treated cells [ 46 ]. Adrenomedullin 2, another CGRP member, increased glioma cell invasion and proliferation via enhancing the formation of filopodia, which depends on the activation of Erk1/2 pathway [ 47 ]. In this study, ADM expression has been found upregulated in TMZ -resistant glioma samples, suggesting the underlying effect of ADM on glioma cell TMZ resistance.…”
Section: Discussionmentioning
confidence: 99%
“…ADM has been reported as one of 5 candidate genes associated with glioma resistance to TMZ, which showed to be consistently linked to higher expression of DDIT4 and lower prognosis in TMZ-treated cells [ 46 ]. Adrenomedullin 2, another CGRP member, increased glioma cell invasion and proliferation via enhancing the formation of filopodia, which depends on the activation of Erk1/2 pathway [ 47 ]. In this study, ADM expression has been found upregulated in TMZ -resistant glioma samples, suggesting the underlying effect of ADM on glioma cell TMZ resistance.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, GBM had the highest expression of ADM2 . The ADM2 promoted GBM cell proliferation by activating ERK1/2 phosphorylation [ 57 ]. BMP2 and BMP8 are ligands of the transforming growth factor- β (TGF- β ) family [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…AM2 expression increased and correlated with higher-grade gliomas [ 222 ]. AM2 promotes filopodia formation, increasing the invasive capacity of glioma cells, and the activation of ERK1/2 has been involved in the proliferation, invasion, and malignancy of glioblastoma cells [ 222 ].…”
Section: Involvement Of the Tachykinin And Calcitonin/calcitonin Gene...mentioning
confidence: 99%